Studi Perilaku Harian Rusa Timor (Cervus timorensis) di Kawasan Savana Bekol Taman Nasional Baluran Situbondo - Bayuda Luqman Alfarisi; Amaliya Nailatul Musyarrafah (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2023)
Baluran National Park is a conservation area with a climate and geography that supports the formation of dry savanna on the island of Java, so it is also known as "Little Africa in Java". The purpose of this study was to determine the daily behavior of the Timor deer (Cervus timorensis) in the Bekol Savana area, TN. Baluran, Situbondo Regency, East Java Province. The data collection technique was conducted through direct observation for one week in February 2023 using the time sampling method, accompanied by literature studies and interviews. Observations were made in three periods (morning-afternoon-evening) with an interval of 2 hours each period with an interval of 10 minutes. The results showed that the daily behavior of Timor deer was eating 19,84%, drinking 1,1%, standing 31.29%, walking 17.55%, running 2,92%, alert 12.59%, affiliative 2.31%, maternal 0,02%, playing 0.13%, and 0,13% vocalization. The most dominant daily behaviour of Timor deer is standing, with a frequency of 1.394 times (31,29%). Keywords: baluran national park; daily behavior; timor deer.